Synchrotron-based NEXAFS analysis of thermal-treated diamond-like carbon films - Chunjaemsri, Thanun; Chanlek, Narong; Sukkha, Usa; Nakajima, Hideki; Rujirawat, Saroj; Yimnirun, Rattikorn; Kidkhunthod, Pinit (My University, 2020)
Diamond-like carbon (DLC) film properties are known to vary with important factors such as the ratio of sp3 to sp2 hybridization, film thickness, and contaminations. In this work, the carbon bonding contents in DLC thin films, thermal-treated with various temperatures between room temperature to 250 °C, were studies by near-edge X-ray absorption fine structure (NEXAFS), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. From NEXAFS measurements, the sp3/sp2 ratios of DLC films were found to be unaffected by the thermal treatments. The results indicate that thermal treatment below 250 °C does not affect the carbon bonding contents in DLC thin film.
Keywords: DLC films; NEXAFS; Raman spectroscopy; X-ray photoelectron spectroscopy